Development of a Mobile Learning Application for Integral Topics Using the Mechanics, Dynamics, and Aesthetics (MDA) Gamification Approach - Triana Harmini; Dihin Muriyatmoko; Muhammad Shofar Riduantara (Riemann: Research of Mathematics and Mathematics Education, 2026)
Learning integral topics in calculus courses is characterized by a high level of complexity, which often leads to low student motivation and limited engagement in the learning process. Gamification in mathematics education has been recognized as an effective approach to enhance learning interaction, particularly for abstract and procedural topics such as integrals; however, the application of a structured gamification framework, specifically mechanics, dynamics, and aesthetics (MDA), in mobile-based calculus learning remains limited. This study aims to develop an Android-based mobile learning application for integral topics by implementing the MDA gamification approach. The research employs the Software Development Life Cycle (SDLC) using the Waterfall model, which consists of requirement analysis, design, implementation, testing, and maintenance stages, involving 34 second-semester students of the Informatics Engineering Study Program as research subjects. The application was evaluated through black-box testing, functional testing, and expert validation. The validation results indicate that the application is categorized as very feasible, with an average score from material experts of 96% and a score from media experts of 95.65%. These findings demonstrate that the MDA-based gamified mobile learning application is highly suitable from both material and media aspects and can serve as an alternative learning medium to support calculus learning, particularly for integral topics.